Indole Hydrazide Compound IHZ-1 Induces Apoptosis and Autophagy via Activation of ROS/JNK Pathway in Hepatocellular Carcinoma - Sun, Manting; Liu, Dan; Yuan, Yang; Dan, Juhua; Jia, Shuting; Luo, Ying; Liu, Jing (Frontiers in Oncology, 2022)
Hepatocellular carcinoma is one of the most common primary malignant tumors of digestive system. Compound 5-chloro-N'-(2,4-dimethoxybenzylidene)-1H-indole-2-carbohydrazide (IHZ-1/ZJQ-24) is a novel indole hydrazide derivative. In recent study, we demonstrated IHZ-1 inhibits tumor growth and induces cell apoptosis through inhibition the kinase activity of mTORC1 without activation of AKT, which is associated with JNK/IRS-1 activation. However, the impact and mechanisms of JNK activation by IHZ-1 in hepatocellular carcinoma remains entirely unknown. Here, we find that IHZ-1 increase the generation of intracellular ROS and enhances autophagy. The phosphorylation of JNK indcuced by IHZ-1 was reversed by the decreased ROS level. Moreover, inhibition ROS/JNK or autophagy equally attenuated apoptotic effect induced by IHZ-1. Our findings suggest that the activation of JNK by IHZ-1 treatment is dependent on the generation of ROS that mediates apoptosis and autophagy in hepatocellular carcinoma.